Aktualisasi Perempuan Hindu Dalam Jejaitan, Banten Dan Upakara Sebagai Pelestarian Budaya Dan Kesadaran Estetika Manusia Bali - Putu Agus Yasa Windu Bukian; Desak Ketut Sugiartini; Putu Dian Prima Kusuma Dewi (Jayapangus Press, 2020)
The purpose of this research in the long term is to analyze the actualization of Hindu women in Bali in matching, making offerings and performing ceremonies. The specific objective is to analyze the knowledge, attitudes, perceptions, practices and skills of Hindu women in matching, making offerings and ceremonies in their simplest form. This type of research is a mix method research with an ethnographic approach. The research instruments were questionnaires and interview sheets. Quantitative data analysis uses chi square and logistic regression, and qualitative data uses reduction analysis or thematic analysis. The research was carried out as follows: knowledge, attitudes, and practices were traced using a questionnaire sheet. Indept interview to find out in depth the perceptions and practices of aligning, making offerings, and the implementation of the ceremony which was carried out in Kubutambahan. The results show that 93.14% of Balinese Hindu women have good actualization in preserving the culture of jejaiatan, banten and upakara in Bali. The skills of Balinese women in terms of jejitan, offerings and ceremonies were classified as good, respectively, at 94.86%, 45.71%, and 92%. Knowledge, attitudes and practices in sequence related to jejitan, offerings and upakara, good knowledge 97.14%, 89.71%, 94.86%, negative attitudes 64%, positive 68%, 53.71%, practice carried out correctly 97.14%, 97.71%, and 94.86%. Jejaitan as an important element before understanding the concept of offerings and upakara. jejaitan, banten and upakara are the cultural heritage of Balinese women created by the social community as a very important and worthy cultural heritage. These three components are a form of yadnya for Hindu women in Bali.